Community-Based Tourism as a Strategy for Economic Empowerment of Suntenjaya Village - Darmawangsa (Institute of Computer Science (IOCS), 2021)
Tourism is one type of labor-intensive industry that is able to encourage all aspects of community problems, starting from economic, social, cultural, and other aspects that affect the community. One of the developments of tourism through the concept of community base tourism (community-based tourism) is tourism development where all tourist activities take place and mingle with rural communities. Management of this form of CBT, the community will have a sense of belonging to tourist attractions both in terms of planning, management, and development. It aims to help tourists achieve satisfaction in tourism. the management of the CBT model is also able to improve the welfare of local communities in tourist attractions from various sectors. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that Suntenjaya Village, also known as Batu Loceng Village, has a relatively original tradition and culture. This condition can be observed from the structure of people's houses, typical food, agricultural systems, arts, crafts, traditions, rituals, myths, religions, and other local wisdom. This tourist village prioritizes local wisdom and teaches its people ethics and moral values ​​such as mutual cooperation, tolerance, protecting and preserving nature, and respecting their own culture by protecting nature and culture. This tourist village began to develop because of the idea of ​​the Batu Loceng kabuyutan figure. In the tourism program, tourists are invited to enjoy a variety of arts, food, performances, farming patterns, games and even the structure of the traditional house of the local community that still maintains local wisdom